2018
DOI: 10.21474/ijar01/8174
|View full text |Cite
|
Sign up to set email alerts
|

Sheep and Goats Toxoplasmosis Prevalence in Northern Borders Areas of Cote D?ivoire: Case of Bagoue and Tchologo Regions.

Abstract: Kiffôpan b. M'bari 1 , biégo g. Gragnon 2 , edouard k. N'goran 3 , olivier g. Ouina 3,4 and guy-gérard k. Kouame 5 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…This study showed that Malang Regency had higher toxoplasmosis prevalence than Lumajang Regency, indicating that seroprevalence was influenced by location. Other studies have reported that the seroprevalence of toxoplasmosis is correlated with location [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study showed that Malang Regency had higher toxoplasmosis prevalence than Lumajang Regency, indicating that seroprevalence was influenced by location. Other studies have reported that the seroprevalence of toxoplasmosis is correlated with location [ 17 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The same study reported that the presence of cats and domestic animals and access to drinking sources for livestock are risk factors for toxoplasmosis [ 4 , 11 ]. The serological and risk factors affecting toxoplasmosis in goats and sheep are presented in Table-4 [ 4 , 17 20 , 28 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation